The Nationalist Republican Party of Évora (1923-1935) - ideology, regional policy, internal organization and elites - Baiôa, Manuel (2006)
This article seeks to explain the success of the Nationalist Republican Party in the final years of the First Republic in the Évora region on the basis of an analysis of ideology, regional politics, internal organization and the elites. It also seeks to put forward some ideas to explain its decline and demise during the military dictatorship and the Estado Novo.